Evaluation of the physicochemical quality of raw milk from cattle farms in the region of Djelfa (Algeria) - Hamiroune, Mourad; Kouskous, Mohamed; Kebaili, Abderrazek Nezzar (International journal of Horticulture, Agriculture and Food science, 2020)
Milk is a food of animal origin. In is an important source of nutrients in humans. For this, in order to know the physicochemical quality of raw milk from cows of local and improved breed, a study was carried out on thirty nine samples of raw milk were taken from cattle farms in the region of Djelfa in Algeria. The results showed that cow's milk had 3.30 ± 0.54% fat (FT), 8.89 ± 2.05% non-fat dry matter (NFDR), 3.45 ± 0.73% protein (PR), 5.02 ± 1.07% lactose (LC) and a density (DS) of 1.0272 ± 0.0078 with a freezing point (FP) -0.2971 ± 0.0528 ° C and a pH of 6.57 ± 0.24. The study of the relationship between temperature (TS) and physicochemical indicators has shown the existence of seven weak correlations. Six correlations are negative [pH-TS (r = -0.1258, R2 = 0.0158); NFDR-TS (r = -0.0551, R2 = 0.0030); PR-TS (r = -0.0273, R2 = 0.0007); LC-TS (r = -0.0467, R2 = 0.0022); DS-TS (r = -0.0323, R2 = 0.0010); FP-TS (r = -0.0309, R2 = 0.0010)] and a correlation is positive [FT-TS (r = 0.0279, R2 = 0.0008)]. In addition, the average temperature is 15.53 ± 5.80 ° C. In parallel, these temperatures in the majority of cases are greatly exceeded the values recommended by Algerian standards (+ 6 ° C). These results reflect risks to the health of consumers. Finally, it will be very useful to carry out a program to improve the food ration on all farms in the country; this will help improve the quality and quantity of raw milk but would also improve Algeria's independence vis-à-vis foreign countries in terms of imports of milk, thereby ultimately providing benefits for all economy of the country.